Sex Selection and the Procreative Liberty Framework - de Melo-Martín, Inmaculada (Kennedy Institute of Ethics journal, 2013)
The practice of sex selection for social reasons has raised serious criticism. Advocates of this practice, however, insist that objections to it are unfounded and that legal bans are ethically unjustified. Usually, proponents use a rights-based liberal approach as the framework to evaluate this practice. Under this framework, reproductive choice is a basic freedom and interference with individuals’ autonomous reproductive choices is illegitimate, unless their actions are shown to seriously harm others. As persuasive as this framework might be in relation to many aspects of reproduction, I argue that it is inappropriate when dealing with sex selection for social purposes.